Controlling factors of benthic macroinvertebrates distribution in a small tropical pond, lateral to the Paranapanema River (São Paulo, Brazil) - Shimabukuro, Erika Mayumi [UNESP]; Henry, Raoul [UNESP] (FapUNIFESP (SciELO), 2011)
Aim: The aim of the present study was to examine the benthic fauna in a marginal pond lateral to the Paranapanema River and to identify the main controlling factors of its distribution. Considering the small size of the lacustrine ecosystem, we expected that seasonal variations of the benthic community attributes are more important than spatial variations; Methods: Two samplings, one in March and another in August, were carried out at nine sites in the pond. Sediment samples were obtained through a Van Veen grab for invertebrate sorting, granulometric analysis, and for quantification of organic matter in sediment. Other abiotic factors were measured, such as water transparency, dissolved oxygen, pH, electric conductivity, temperature, and depth of sediment sampling sites. Regarding the comparative analysis at spatial scale, no significant variations in density of the benthic invertebrate community were found. Results: In relation to the studied abiotic factors, only depth presented significant differences among sampling sites; All the measured environmental parameters presented significant differences among sampling months, except depth and the physical and chemical characteristics of the sediment. The abundance of Chaoboridae and Chironomidae was the unique attribute with a significant difference in comparing the two months. A higher abundance of taxa occurred in August, especially for Oligochaeta, Nematoda, Chaoboridae, and Chironomidae; Conclusions:Because of the low structural complexity of the studied pond, we concluded that the changes in benthic macroinvertebrate community attributes were mainly due to seasonal effects.
Macroinvertebrados bentônicos e fatores controladores de sua distribuição em uma pequena lagoa tropical adjacente ao rio Paranapanema (São Paulo, Brasil)
Keywords: Benthic fauna; Environmental variables; Marginal pond; Spatial variation; Temporal variation